Effect of Security Measures on Business Performance of Tourism Entrepreneurs in National Museum Lagos, Nigeria - OLABOSINDE, Samuel Taiwo; KASSAH, Virginia (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study investigates the impact of security measures on the performance of tourism businesses operating in the vicinity of the National Museum Lagos, Nigeria. The objective is to assess how four distinct security dimensions—policy and regulatory frameworks, physical security measures, operational security practices, and technological security measures—influence tourism business performance. A quantitative research design was adopted, and data were collected through structured questionnaires administered to 150 tourism entrepreneurs, selected using stratified random sampling from a known population of 250 businesses. To test the study hypotheses, multiple regression analysis, an inferential statistical method, was employed to evaluate the relationship between the independent variables and business performance outcomes. The results indicate that policy and regulatory measures had a positive and statistically significant effect on performance (B = 0.221, p = 0.018), emphasizing the critical role of clear, enforceable legal frameworks in supporting tourism entrepreneurship. However, physical security measures had a significant negative impact (B = -0.404, p < 0.001), suggesting inefficiencies or misallocations in security resource deployment. Both operational security practices (B = 0.100, p = 0.484) and technological security measures (B = -0.328, p = 0.786) showed no statistically significant influence, implying underutilization or misalignment with operational needs. The findings suggest a need for balance between regulatory enforcement and visitor-friendly security implementations. The study concludes that while legal and regulatory measures can drive business performance, overdependence on physical security without corresponding efficiency may hinder outcomes. Implications of the research are relevant for policy-makers, tourism entrepreneurs, and security professionals, guiding them toward cost-effective and performance-enhancing security strategies. The study contributes to existing literature by offering context-specific empirical evidence and theoretical grounding through the Theory of Planned Behavior, filling a notable gap in security-performance research within Nigeria’s heritage tourism sector.